Peran Financial Performance Dalam Memediasi Pengaruh Good Corporate Governance Terhadap Financial Distress - Nur Aeni; Meilani Purwanti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study analyzes the effect of Good Corporate Governance (GCG) on Financial distress with Financial performance as a mediating variable in industrial sector companies listed on the IDX for the period 2020–2023. The background of this study is based on increasing business competition due to cheap products from China, which caused the closure of 30 factories during that period. This study uses secondary data from financial reports of public companies with a purposive sampling method, resulting in 52 samples. Data analysis was carried out through regression and the Sobel test using SPSS 29. The results showed that GCG had no effect on Financial performance (p = 0.240), Financial performance had a negative effect on Financial distress (p = 0.000), and GCG had a negative effect on Financial distress (p = 0.035). However, Financial performance did not mediate the relationship between GCG and Financial distress (p = 0.254).